Health Care and Aboriginal Seniors in Urban Canada: Helping a Neglected Class - Beatty, Bonita Beulah; Berdahl, Loleen (International Indigenous Policy Journal, 2011)
Canadian researchers and policymakers have paid limited attention to the health care needs of Aboriginal seniors. This lack of attention is problematic, as the situation of Aboriginal seniors – including both status and non-status First Nations, Métis and Inuit – is particularly bleak. Using Winnipeg, Regina and Saskatoon as examples, this paper analyses the health care challenges facing Aboriginal seniors in urban Canada. We ask, what policy approaches are needed to improve the health and wellbeing of urban Aboriginal seniors so that they can have good quality living reflective of their needs and culture? We suggest that, in thinking through present and future health services for urban Aboriginal seniors, policymakers should consider four key factors: socioeconomic conditions; underutilization of urban health services; jurisdiction; and elder abuse.